2019
DOI: 10.7554/elife.46393
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput, single-particle tracking reveals nested membrane domains that dictate KRasG12D diffusion and trafficking

Abstract: Membrane nanodomains have been implicated in Ras signaling, but what these domains are and how they interact with Ras remain obscure. Here, using single particle tracking with photoactivated localization microscopy (spt-PALM) and detailed trajectory analysis, we show that distinct membrane domains dictate KRasG12D (an active KRas mutant) diffusion and trafficking in U2OS cells. KRasG12D exhibits an immobile state in ~70 nm domains, each embedded in a larger domain (~200 nm) that confers intermediate mobility, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 66 publications
4
51
0
Order By: Relevance
“…dimer through residue D113 in the loop 4 region could form a kinetic proofreading platform similar to that observed for the LAT/Grb2/SOS complex 28,46-48 . Biocondensates, consisting of concentrated multiprotein assemblies forming distinct fluid structures that separate from surrounding areas, are ubiquitous across signal transduction networks 49 . Furthermore, single particle tracking (SPT) experiments 50,51 , most recently coupled with photoactivated localization microscopy (SPT-PALM) and detailed trajectory analysis 52 , have shown that activated Ras proteins in live cells are found on the membrane in mobile and immobile phases, the latter being consistent with the predicted formation of large macromolecular assemblies that cannot freely diffuse on the membrane. Recent work with the transmembrane receptor LAT and its cytosolic binding partners Grb2 and the Ras guanine nucleotide exchange factor SOS, have shown that these proteins form polymer-like assemblies on supported lipid bilayers 46 , with restricted mobility.…”
Section: Simulations Of the Kras/craf-rbd Dimer On The Membranementioning
confidence: 83%
See 1 more Smart Citation
“…dimer through residue D113 in the loop 4 region could form a kinetic proofreading platform similar to that observed for the LAT/Grb2/SOS complex 28,46-48 . Biocondensates, consisting of concentrated multiprotein assemblies forming distinct fluid structures that separate from surrounding areas, are ubiquitous across signal transduction networks 49 . Furthermore, single particle tracking (SPT) experiments 50,51 , most recently coupled with photoactivated localization microscopy (SPT-PALM) and detailed trajectory analysis 52 , have shown that activated Ras proteins in live cells are found on the membrane in mobile and immobile phases, the latter being consistent with the predicted formation of large macromolecular assemblies that cannot freely diffuse on the membrane. Recent work with the transmembrane receptor LAT and its cytosolic binding partners Grb2 and the Ras guanine nucleotide exchange factor SOS, have shown that these proteins form polymer-like assemblies on supported lipid bilayers 46 , with restricted mobility.…”
Section: Simulations Of the Kras/craf-rbd Dimer On The Membranementioning
confidence: 83%
“…Other interactions with the membrane from within these condensates, for example involving membrane receptors 53 , SOS [54][55][56] or PLCg 57 , further restrict molecular mobility and may influence Ras. Increasing connectivity with dimerization of the Ras/Raf complex could allosterically prime the Galectin binding site on Raf-RBD, to form a multivalent protein complex on the membrane corresponding to the immobile species observed in the SPT-PALM experiments 52 . This platform of synchronized activated signaling proteins (Fig.…”
Section: Simulations Of the Kras/craf-rbd Dimer On The Membranementioning
confidence: 98%
“…The spatial mapping of the state coordinates showed that the slow and intermediate diffusion states cluster within nested nanoscopic domains of 200 nm and 70 nm for the intermediate and slow states, respectively [ 21 ], further confirming that RAS is exploring a hierarchical membrane structure. The formation of these states follows a nonequilibrium steady state where immobile KRAS molecules are endocytosed, and the endomembrane recycling system replenishes the fast-moving KRAS molecules.…”
Section: Membrane Organization Ras Dynamics and Ras Clusteringmentioning
confidence: 93%
“…Recently, work using improved imaging techniques and more photostable fluorescent tags indicates that KRAS membrane dynamics can be described by a three-state diffusion model ( Figure 4 A,B) [ 20 , 21 ]. In this model, KRAS4b diffusion in the plasma membrane is described by fast (~1 μm 2 /s), intermediate (~0.2 μm 2 /s) and slow (~0.05 μm 2 /s) diffusion states.…”
Section: Membrane Organization Ras Dynamics and Ras Clusteringmentioning
confidence: 99%
“…The high-affinity Ras-Raf's RBD interaction, enhanced by CRD membrane attachment (Fang et al, 2020;Li et al, 2018aLi et al, , 2018bOkada et al, 1999;Sarkar and Garcia, 2020;Travers et al, 2018), shifts Raf's equilibrium toward the open state and interaction with Ras (Nussinov et al, 2019a). RBDs' interactions with spatially proximal Ras catalytic domains in Ras dimers or nanoclusters promote Raf's KD dimerization and activation (Holderfield et al, 2014;Lavoie et al, 2013;Lee et al, 2019;Muratcioglu et al, 2015Muratcioglu et al, , 2020. Active Raf phosphorylates MEK1/2 (MAPK kinase 1/2) (De Luca et al, 2012;Young et al, 2013), with signaling propagating down the mitogen-activated protein kinase (MAPK) pathway to activate extracellular signal-regulated kinase (ERK) and transcription factors, such as Elk-1 (Gao et al, 2019;, with the resulting expressed proteins entering the G 1 phase of the cell cycle, thereby linking the cellular environment to cell-cycle progression.…”
Section: Ras: An Overviewmentioning
confidence: 99%